REKOMENDASI DESIGN ANALISIS KREDIT MIKRO MELALUI EVALUASI PENYEBAB KEBANGKRUTAN DAN KESALAHAN PENDEKATAN DEBITUR - Wahyudiono, Bambang (Universitas Pakuan, 2016)
ABSTRACTMicro entrepreur that commons calls as small medium entreprise have unique characteristics. This is difference to type of corporations with all instrument embeded that can be evaluated. Accuracy of their instruments and documented information, enable to analyze more valid. This is differ whith micro business. Unpredictable their condition will impact to poor result analysis done by financial institutions. Non performing loan or NPL is main indicator that show credit or loan problems. Banckruptcy is the worst conditions when micro credit on NPL categories. In this research, we try to identify some factor above for improvement design or process of analysis micro credit. Micro business banckruptcy conditions not only unproper approach for financial institution but also unappropriate empowerment for micro business.Key words: Small business scale, credit analysis, over financing, interest rate, trial business, unsucced expansion, management, leadership, banckruptcy, repayment capacity, phase out strategy.